Formulation - Properties effects of novel dual composite hydrogels for use as medical sealants. (5th June 2021) - Eshkol-Yogev, Inbar; Gilboa, Efrat; Giladi, Shir; Zilberman, Meital
Graphical abstract: Highlights: Novel "Dual composite hydrogels" are presented for medical sealants applications. The hydrogels are loaded with two functional fillers: MMT and cellulose fibers. Incorporation of the fillers, improve hydrogel's mechanical and physical properties. The dual composite presents high biocompatibility with excellent sealant ability. Abstract: Use of sealants for wound closure and healing applications is being widely investigated due to their many advantages. However, currently available surgical sealants do not combine high strength with biocompatibility and other desired properties. We recently developed and studied hydrogels based on the natural polymers gelatin and alginate. In the current study, two functional fillers, the hemostatic agent montmorillonite and cellulose fibers, were incorporated into a basic formulation to create novel "dual composite" medical hydrogel sealants. The effects of both functional fillers on the mechanical and physical properties of the hydrogels as well as their microstructure and cytotoxicity were studied. Moreover, a qualitative model on the mechanical and physical properties of the hydrogels was developed. Incorporation of montmorillonite and cellulose fibers resulted in a significant increase in the tensile strength and modulus, better sealing ability, higher viscosity and lower gelation time and swelling degree. These changes were mainly due to dispersion of montmorillonite into nanoparticles within the hydrogel and physical crosslinking of the gelatin molecules. The cellulose fibers contributed by their reinforcing effect and ability to absorb water, and probably also by entanglements of the polymeric structure. Understanding the effects of each functional filler on the mechanical and physical properties in both liquid and solid states enables fitting desired formulations to specific medical applications. Together with the excellent biocompatibility of these dual composite hydrogels, they are expected to successfully be used as bioadhesives and medical sealants in various applications.